Remodeling of the HDL proteome with treatment response to abatacept or adalimumab in the AMPLE trial of patients with rheumatoid arthritis. (August 2018) - Charles-Schoeman, C.; Gugiu, G.B.; Ge, H.; Shahbazian, A.; Lee, Y.Y.; Wang, X.; Furst, D.E.; Ranganath, V.K.; Maldonado, M.; Lee, Terry; Reddy, S.T.
Abstract: Background and aims: To evaluate changes in the high-density lipoprotein (HDL) proteome and HDL function in active rheumatoid arthritis (RA) patients initiating therapy with abatacept or adalimumab in the Abatacept Versus Adalimumab Comparison in Biologic-Naïve RA Subjects with Background Methotrexate (AMPLE) study. Methods: Ultra high-pressure liquid chromatography (UHPLC) coupled with ion mobility mass spectrometry (LC-IM-MS) was used to analyze proteins associated with immunoaffinity-captured HDL from plasma of 30 patients with RA randomized to either abatacept (n = 15) or adalimumab (n = 15) therapy. Paraoxonase 1 (PON1) activity, HDL anti-oxidant capacity, cholesterol profiles, and homocysteine levels were also measured at baseline and following treatment. Repeated-measures analyses were performed using mixed-effect linear models to model the within-subject covariance over time. Results: In models controlling for age, sex and treatment group, improvement in inflammation measured by decreases in CRP was associated with improvement in HDL function and changes in several HDL-associated proteins including significant decreases in lipopolysaccharide-binding protein, serum amyloid A-I (SAA-I) and inter-alpha-trypsin inhibitor heavy chain H4 ( p values < 0.05). Improvement in disease activity was also associated with changes in multiple HDL-associated proteins. Adalimumab was associated with higher PON1 activity, HDL-associated serotransferrin, and HDL-associated immunoglobulin J chain, and lower HDL-associated SAA-I over time compared with abatacept. Conclusions: Improvement in inflammation associated with treatment of RA, using either abatacept or adalimumab in the AMPLE study, was associated with improvement in HDL function and significant alterations in the HDL proteome, including proteins involved in the immune response, proteinase inhibition, and lipid metabolism. Highlights: Patients with rheumatoid arthritis (RA) have high cardiovascular (CV) risk. Increased CV risk in RA patients is associated with high RA disease activity. The HDL proteome is abnormal in active RA patients. Treatment of RA was associated with improvement in HDL function. Treatment of RA was associated with favorable changes in the HDL proteome.